A Comprehensive Error Analysis of the Neutron Elliptical Cylindrical Mirror with High Gain - Weichen Gu; Jun Yu; Pengfeng Sheng; Fengrui Tang; Qiya Zhang; Peng Chen; Qiaoyu Wu; Wentao Song; Zhangran Cao; Zhengxiang Shen; Zhong Zhang; Zhanshan Wang (Photonics)
The elliptical cylindrical mirror has been utilized in neutron small-angle scattering and reflectometry to enhance the neutron intensity at the sample position. However, the performance of the elliptical cylindrical mirror can be impacted by surface slope errors, reflectivity, and misalignments. In this work, the performance of the elliptical cylindrical mirror under different error conditions has been analyzed comprehensively, and a 250-mm-long elliptical cylindrical mirror was designed and developed. The simulations show that a source size below 1 mm is required to achieve a peak gain above 6, with a theoretical peak gain of 16× with a 0.1 mm source. The rotational misalignment of 0.03° around the Y-axis can decrease gain from 16× to 6×. The designed mirror was fabricated with a surface figure error of 110 nm (RMS), and a roughness below 0.5 nm (RMS), and was coated with an m = 4 supermirror. The mirror was aligned and tested in the dedicated neutron beamline of the Chinese mianyang research reactor, and the results show a peak gain of 12.77 with a 0.1 mm slit source.